Implementation Licencing Regulations Telecommunications Network in The Omnibus Law - Jumhur, helni; Hikmaturokhman, Alfin (Buletin Pos dan Telekomunikasi, 2023)
The form manifestation of the omnibus law form is Law Number 11 of 2020 concerning Copyright. The law on telecommunications relating to Main Licensing and Technical Licensing has undergone significant changes. Implementing the licensing process requires changes and a common perspective in understanding the articles associated with the licensing process, especially in telecommunications. The problem experienced is that several articles in the omnibus law regarding licensing for the operation of telecommunications networks still need to be clarified, which can potentially cause different perceptions among stakeholders. This study uses a normative juridical analysis method using primary law to analyze the problems that are the focus of the research. The conclusion drawn from this research is the need to clarify the articles in Law 11 of 2020 concerning Job Creation and its derivative regulations regarding procedures for telecommunications operations other than those that already exist, which a Ministerial Decree can stipulate. There needs to be clarity in the rules regarding risk-based business licensing regarding how long the essential and technical licensing process takes and the need to attach a licensing SOP flowchart so that licensing stakeholders have the same perception of the licensing process.